Understanding identity & organizations - Kenny, Kate (SAGE, 2011)
An understanding of identity is fundamental to a complete understanding of organizational life. While conventional management textbooks nod to in-groups, cohesion and discrimination, this text offers instead a deeper, more nuanced understanding of why people, groups and organizations behave the way they do.